Menebus Dosa Masa Lalu: Ekoliterasi Pada Anak Sebagai Penyadaran Lingkungan - Iqbal Muttawakkil; Maulana S. Kusumah (JSPH (Jurnal Sosiologi Pendidikan Humanis), 2020)
Using the wrong fishing gear causes the Bangsring beach environment to become damaged. This environmental damage has created local heroes to restore the environment to its original state. This research is a qualitative study using a life history case study approach. Researchers use Derrida's deconstruction as a tool for analyzing phenomena. Researchers focused on Ikhwan Arif's thoughts as a process of environmental awareness for coastal communities in Bangsring Village, Wongsorejo in Banyuangi Regency. The results of this study explain that there is environmental awareness by means of socialization related to the importance of protecting the marine environment to objects around fishermen, namely through children, in local nuances this socialization is also referred to as marine education. The process of providing this material is used to provide understanding and knowledge related to the environment (ecoliteration). The presence of the marine education program is used as a way to atone for past sins committed by fishermen for exploiting the marine environment. In the marine education process, children are given knowledge about the marine environment and how to manage it. Ecoliteration is not only seen as a form of education about the environment. On a different side, there are other things that can be seen from the ecoliteration of children, namely making children as agents to help change fishermen's fishing patterns. Children are chosen to be agents because children are considered as individuals who dare to express opinions, individuals who are easily formed, and individuals who must be cared for who will continue the next generation. Penggunaan alat tangkap yang salah menyebabkan lingkungan pantai Bangsring menjadi rusak. Kerusakan lingkungan tersebut memunculkan local heroes untuk mengembalikan lingkungan seperti semula. Penelitian ini merupakan penelitian kualitatif dengan metode pendekatan studi kasus life history. Peneliti menggunakan dekonstruksi Derrida sebagai pisau analisis fenomena. Peneliti memfokuskan pada pemikiran Ikhwan Arif sebagai proses penyadaran lingkungan masyarakat pesisir di Desa Bangsring, Kecamatan Wongsorejo, Kabupaten Banyuwangi. Hasil penelitian menjelaskan bahwa terdapat penyadaran lingkungan dengan cara sosialisasi terkait pentingnya menjaga lingkungan laut kepada objek disekitar nelayan yaitu melalui anak-anak, dalam nuansa lokal sosialisasi ini juga disebut sebagai marine education. Proses pemberian materi ini digunakan untuk memberikan pemahaman dan pengetahuan terkait dengan lingkungan (ekoliterasi). Hadirnya progam marine education digunakan sebagai cara untuk menebus dosa di masa lalu yang dilakukan nelayan karena telah mengeskploitasi lingkungan laut. Dalam proses marine education, anak diberikan pengetahuan tentang lingkungan laut dan cara menjagannya. Ekoliterasi tidak hanya dilihat sebagai sebuah bentuk edukasi tentang lingkungan saja. Disisi yang berbeda, terdapat hal lain yang dilihat dari ekoliterasi pada anak, yaitu menjadikan anak sebagai agen untuk membantu merubah pola tangkap nelayan. Anak dipilih menjadi agen karena anak dianggap sebagai individu yang berani untuk mengungkapkan pendapat, individu yang mudah dibentuk, dan individu yang harus dijaga yang akan meneruskan generasi selanjutnya